Program SEJENAK (Sigedang Edukasi Jelajah Anak) untuk Mengurangi Penggunaan Gadget di Kalangan Anak Desa Sigedang Kejajar Wonosobo - Maesaroh, Maesaroh; Huda, Muhammad Nur; Azizah, Mir’atun; Rofiqoh, Rizkiyana; Khasanah, Irma Nur; Ihsanuddin, Imam Ahmad (Jurnal Pengabdian Masyarakat PGSD, 2023)
The use of gadgets among children makes it difficult to control the intensity of gadget use. This is what parents in Sigedang Village, Kejajar District, Wonosobo Regency, Central Java. Apart from that, the potential of Sigedang Village has not been properly explored. The community service aimed to determine the effectiveness of a SEJENAK Program in reducing the use of gadgets among children in Sigedang Village, Kejajar sub-district, Wonosobo Regency. The service is to find out the percentage of decreased time for playing with gadgets by children in Sigedang Village and to find out children's responses to Generation Z-based playgrounds in the village of Sigedang Kejajar Wonosobo through the program. The community service methods used are counseling and education programs in the form of surveys, interviews, distribution of questionnaires to parents to find out the intensity of gadget use in children, and literature studies from various sources such as journals, theses, books, and theses both nationally and internationally regarding similar research that supports arguments and result of the program. The results of the SEJENAK program show that there is a decrease in the level of Gadget use after a moment. The intensity of the decrease in gadget use is from 3 hours per day to 0.5 hours per day. The SEJENAK Program can reduce the level of anxiety of parents in Sigedang Village about the side effects of using gadgets on children